Retóricamente persuasiva - Lasso de la Vega González, Carmen (Questiones publicitarias, 2000)
<!--[if gte mso 9]> 0 0 1 4 24 dtp 1 1 27 14.0 <![endif]--> <!--[if gte mso 9]> Normal 0 21 false false false ES-TRAD JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> <!--StartFragment--> Nocionessobrelaretórica <!--EndFragment-->